2022
DOI: 10.1111/sjop.12813
|View full text |Cite
|
Sign up to set email alerts
|

Stress appraisal as a mediator between the sense of coherence and the frequency of stress coping strategies in women and men duringCOVID‐19 lockdown

Abstract: The COVID‐19 lockdown experience is a unique and unexpected stressful life situation. In our research project, we explored gender differences in the mean level of stress appraisal (SAQ), the frequency of stress coping strategies (COPE), and the sense of coherence (SOC), as well as gender differences in the strength of the relationships between SAQ, COPE, and SOC during the COVID‐19 lockdown. Finally, we tested if stressor appraisal (as a threat, harm/loss, or challenge) mediates the relationship between SOC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 106 publications
1
5
0
Order By: Relevance
“…The increased reliance on spiritual connections could be due to increased levels of stress and anxiety symptoms experienced by female respondents. These findings are explainable as a recent study also reported the significance of gender differences in stress appraisal, levels of the sense of coherence, and stress coping strategies (Lelek-Kratiuk and Szczygieł, 2022). This study endorsed low levels of sense of coherence in women which increased their risk to experience high levels of stress.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The increased reliance on spiritual connections could be due to increased levels of stress and anxiety symptoms experienced by female respondents. These findings are explainable as a recent study also reported the significance of gender differences in stress appraisal, levels of the sense of coherence, and stress coping strategies (Lelek-Kratiuk and Szczygieł, 2022). This study endorsed low levels of sense of coherence in women which increased their risk to experience high levels of stress.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, they reported that women are more likely to employ a variety of coping strategies in comparison to men. However, women use these coping methods less effectively as reported by another study conducted during the COVID-19 pandemic ( Lelek-Kratiuk and Szczygieł, 2022 ) and this may increase their susceptibility to experiencing stress and anxiety. We also observed in this study that women had significantly higher mean scores on spiritual connections as compared to men and simultaneously scored high on the anxiety and stress scale and this susceptibility is further validated in predictive analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies found that both women and girls worried more about pandemic-related health concerns, such as, for example, getting and spreading the virus [ 37 , 51 ], and such worries might well have a detrimental effect on mental health. Similarly, Lelek-Kratiuk and Szczygieł found that women were more likely to evaluate COVID-19-related lockdown as a threat or harm and loss [ 52 ], a finding that might well apply to girls as well. Kaltschik et al offered some hypotheses including girls’ stronger reliance on a social network for emotional support with these networks being reduced by Covid-19-related restrictions of social life, a larger reduction of physical activity levels among girls, and girls’ higher smartphone usage during the pandemic [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, COVID-19 has undeniably acted as an acute and strong source of stress. There is abundant proof that the pandemic was a potentially stressful situation that generated distress in many people, as described in previous paragraphs [2,37,38]. However, the Lazarus and Folkman theory proposes not only risk factors but also protective factors which decrease the negative effects of stress.…”
Section: Covid-19 and Psychological Distress: Protective And Risk Fac...mentioning
confidence: 99%